State-level reforms in India towards more effective government - Howes Stephen; Lahiri Ashok K; Stern Nicholas (Delhi Macmillan India, 2003)
This volume emerged from the papers presented at India States Reform Forum discusses the fiscal and governance reform from a range of perspectives- political, bureaucratic and academic, Indian and foreign, state and national. It is divided into three sec
Keywords: Economic reforms; India